An optimal scheme for top quark mass measurement near the tt¯ threshold at future e+e− colliders *Supported by National Science Foundation of China (11405102) and the Fundamental Research Funds for the Central Universities of China (GK201603027, GK201803019). (May 2018) - Chen 陈, Wei-Guo 卫国; Wan 万, Xia 霞; Wang 王, You-Kai 由凯
Abstract: A top quark mass measurement scheme near the t t ¯ production threshold in future e + e − colliders, e.g. the Circular Electron Positron Collider (CEPC), is simulated. A χ 2 fitting method is adopted to determine the number of energy points to be taken and their locations. Our results show that the optimal energy point is located near the largest slope of the cross section v. beam energy plot, and the most efficient scheme is to concentrate all luminosity on this single energy point in the case of one-parameter top mass fitting. This suggests that the so-called data-driven method could be the best choice for future real experimental measurements. Conveniently, the top mass statistical uncertainty can also be calculated directly by the error matrix even without any sampling and fitting. The agreement of the above two optimization methods has been checked. Our conclusion is that by taking 50 fb −1 total effective integrated luminosity data, the statistical uncertainty of the top potential subtracted mass can be suppressed to about 7 MeV and the total uncertainty is about 30 MeV. This precision will help to identify the stability of the electroweak vacuum at the Planck scale.